Individual and combined effects of electrolyzed water and ultrasound treatment on microbial decontamination and shelf life extension of fruits and vegetables: A review of potential mechanisms. Issue 8 (13th June 2022) - Ahmed, Shafi; Akther, Sharmin; Alam, S. M. Shamiul; Ahiduzzaman, Md.; Islam, Md. Nahidul; Azam, Md. Shofiul
Abstract: Fruits and vegetables deteriorate mostly due to microbial and enzymatic activity during postharvest storage. The objective of the work was to see if electrolyzed water and ultrasound can be applied combinedly in the industry to extend the shelf life of harvested fruits and vegetables. Ultrasound is a novel postharvest treatment method that has the potential to inactivate enzymes and microbes. Pectinmethylesterase, polygalacturonase, peroxidase, polyphenoloxidase, and lipoxygenase are the enzymes that are most commonly deactivated by ultrasound in fruits and vegetables. On the contrary, electrolyzed water is a potential antibacterial agent for fresh fruits and vegetables. Electrolyzed water treatment has some limitations in terms of microbial load reduction, which can be solved using sonication. This article deeply looked into the principles, advantages, disadvantages, and mechanism of action of both techniques. Novelty impact statement: Individual and synergistic effects on shelf life extension of fruits and vegetables were reviewed. In addition, the inactivation mechanisms of microorganisms and enzymes of fruits and vegetables have been explained.